RESEARCH TRENDS TOWARDS TEACHERS’ IN-SERVICE TRAINING - Åžahin, Harun; Akinci, Muhammed (MOJES: Malaysian Online Journal of Educational Sciences, 2020)
This research aims to determine the trends of the studies about in-service teacher training in Turkey. It is a descriptive study using document analysis based on qualitative research method. Various databases were searched and 56 articles about in-service teacher training between 2012 and 2019 were used and included in the study. The data of the study was collected by â€œArticle Classification Formâ€, conceptualized and analysed in terms of its various characteristics within certain themes. According to the findings, there is a decreasing trend in the number of studies between the years of 2012-2019 related to in-service teacher training in Turkey. The studies were mostly carried out in descriptive structures with an unplanned manner during the in-service training of teachers by making urgent decisions. Moreover, the number of comprehensive and planned studies using mixed designs with different participants and multiple data collection and analysis processes is not sufficient. In this context, more emphasis should be given to the studies on in-service teacher training, numbers of which have been decreasing as of 2019, and the possible studies to be carried out should be planned in a comprehensive manner considering the real needs.